Direct evidence of megamammalcarnivore interaction decoded from bone marks in historical fossil collections from the pampean region - Chichkoyan, Karina V. (2017)
Fil: Chichkoyan, Karina V. Universitat Rovira i Virgili. Institut Català de Paleoecologia Humana i Evolució Social; España